Practices and Challenges of Kindergarten Education in Addis Ababa City Administration: Ethiopia - Sisay Wondemetegegn (Ignatianum University Press, 2017)
The intention of this study was to assess the practices and challenges of kindergarten education in Addis Ababa city administration. The core intentions of the study were to check the appropriateness of the instructional material, teacher quality and the physical environment of the schools. For this study, the researcher used a descriptive survey research method and both qualitative and quantitative research approaches were employed. The data gathered from 22 kindergartens, 116 teachers, 21 principals, 5 education quality, audit and inspection experts. The findings of the study revealed that in most kindergartens the key inputs, such as indoor and outdoor materials, were insufficient, there was a lack of qualified human resources and instructional materials, constituting a major bottleneck, awareness creation on the part of stakeholders was low and limited support from educational expertise to private schools were among the challenges. Therefore, Addis Ababa Education Bureau ought to be revising, preparing and distributing curriculum materials based on the interest and developmental level of the children. The city administration, in collaboration with different college and Universities, are supposed to provide training for kindergarten teachers and other personnel to enhance their capacity. In addition, the city administration may promote investors who participate in the sector to construct buildings which may function as kindergartens; "woreda (section of district)" education office in partnership with schools and other stakeholder ought to support small enterprises to produce indoor and outdoor materials. Moreover, joint training, workshops, seminars and awareness amongst pertinent stakeholders should be promoted in a coordinated manner. Keywords: kindergarten, early childhood, preschool